Mind the gap: Platform ethics and competition issues - Rob Nicholls (International Telecommunications Society (ITS), 2017)
The algorithm driven conduct of platform operators ; as the expert handlers of big data ; is starting to challenge the way in which competition law needs to be enforced. Businesses ; especially platform operators ; acquire data and particularly pricing information from other businesses in real-time. This leads to specific potential problems with autonomous actors engaged in algorithmic tacit collusion. These problems are compounded when usual legal tests for collusive price fixing require both a meeting of the minds of the colluding firms and a commitment to the price fixing conduct. It is not clear that bots meet either of these tests. The paper finds that price fixing is unethical using multiple analytical lenses but that the illegality of algorithmic tacit collusion is less clear. By considering the issues associated with concerted practices from a legal and ethical perspective ; the paper charts some approaches that might be applied. It uses changes in competition law in Australia to highlight potential ways of dealing with algorithmic tacit collusion ; but also highlights the potential unintended consequences associated with such changes.
Keywords: 330; Algorithmic tacit collusion; bots; business ethics; cartel conduct; concerted practices; price fixing